Anthropologie politique: Des communautés paysannes de la Sierra Norte de Puebla (Mexique). Deux villages de basse montagne - Durand, Pierre (Anthropologica, 2022)
This paper is a political analysis of two peasant communities of Mexico. It focuses on the different modalities of the "linear model" of hierarchy empirically observed in those communities. The main point of this article is to show the relevance of historical materialism as an approach - long disregarded by anthropologists - for the study of politics.